Assessing the Degree of Determinant Impact on the Management Outcomes of Drug Sensitive Pulmonary Tuberculosis in Sierra Leone-A Case Study of Rural Bo District. - Allieu , Tommy; Tommy BSc, Precious M. (International Journal of Health Sciences, 2023)
Purpose: Treatment outcomes of tuberculosis are strongly influenced by the level of socioeconomic status of a population. Predisposing factors of tuberculosis such as undernutrition, diabetes, and AIDS are hinged on the socioeconomic status of a population. Alcohol, smoking and illicit drug use disorders can predispose to TB especially in hyperendemic setting. Sierra Leone still grapples with socio-economic challenges including all the factors that predispose people to the disease and as well precipitates TB transmission. Methodology: The study was a retrospective cohort study to assess the degree of impact on the determinants of drug sensitive pulmonary tuberculosis treatment outcomes in patients managed in catchment areas in the rural Bo district of Southern Sierra Leone. Data were collected from 2176 participants with even ID numbers enrolled from January 2018 to January 2022 out of the population of 533,900. Sample was calculated at a 99% confidence level and 3% margin of error. Findings: A Chi2 test was performed between age: Î±= <15 yrs Î²= â‰¥15yrs and exit which showed a statistically significant relationship between the two, Ï‡² (4) = 188.32, p = <0.001, Cramr's V = 0.29 with the calculated p-value of <0.001 that is lower than the defined significance level of 5%. There was also a statistically significant relationship between source of income and exit, Ï‡² (12) = 94.57, p = <0.001, There was a statistically significant relationship between food security and exit, Ï‡² (4) = 15.32, p = 0.004, Cramr's V = 0.08. The calculated p-value of 0.004 is lower than the defined significance level of 5%. Unique contribution to theory, practice and policy: Shows that favorable treatment outcomes are a combination of use of chemotherapy, psychosocial care, social, economic and economic moderation strategies especially in the global South where the majority of the patients live in poverty.